2018
DOI: 10.1111/1365-2664.13129
|View full text |Cite
|
Sign up to set email alerts
|

Fertilising semi‐natural grasslands may cause long‐term negative effects on both biodiversity and ecosystem stability

Abstract: Some short‐term experiments in applied ecology and agricultural research have demonstrated that nutrient applications in semi‐natural grasslands can maintain productivity and will not result in the decrease of plant species richness. Such findings may have an impact on management choices and quality of valuable plant communities, and therefore, further discussion of this topic is necessary. We highlight three aspects regarding the management suggestions in grassland communities with high biodiversity: (1) shor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
31
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 54 publications
1
31
0
4
Order By: Relevance
“…This is in accordance with other authors (Melts et al 2018) reporting that intensification of herbage production reduces sward plant diversity while improving its agronomic value.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This is in accordance with other authors (Melts et al 2018) reporting that intensification of herbage production reduces sward plant diversity while improving its agronomic value.…”
Section: Discussionsupporting
confidence: 93%
“…Hence, less productive Arrhenaterion grasslands, such as those limited by soil water availability, are suggested to be fertilized by cattle slurry in the amount up to 120 kg N/ha for a short-term period to meet not only sufficient agronomic objectives, but also nature conservation requirements via maintaining plant diversity (Duffková et al 2015). However, plant species richness would be probably diminished, if suggested management took longer time (Melts et al 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitchell et al (2017) found that in Scottish grasslands over the are likely to be long-lasting (Melts et al, 2018). Mitchell et al (2017) found that in Scottish grasslands over the are likely to be long-lasting (Melts et al, 2018).…”
Section: Chillingham Cattle and Their Botanical And Cultural Enviromentioning
confidence: 99%
“…At Chillingham, AC IV is therefore comparatively species-rich, with more species in a smaller quadrat (25.7 species per 100 m 2 quadrat) and is therefore an important resource of this biodiverse habitat. Mitchell et al (2017) found that in Scottish grasslands over the are likely to be long-lasting (Melts et al, 2018). For example, in arable land in Canada, the effect of a single application of lime on soil pH was still detectable 30 years later (Beckie & Ukrainetz, 1996).…”
Section: Chillingham Cattle and Their Botanical And Cultural Enviromentioning
confidence: 99%